An updated view on the role of the female reproductive tract microbiome in IVF outcomes - N. B. Tursunova; O. P. Lebedeva; O. B. Altukhova; A. V. Nagorny (Акушерство, гинекология и репродукция)
Introduction. In the last decade, a high-throughput 16S ribosomal RNA (rRNA) sequencing allowed to markedly extend insights into female reproductive tract microbiome. However, evidence about its role on in vitro fertilization (IVF) outcomes remains scarce and controversial.Aim: to analyze literature data for assessing an impact of the vaginal, uterine, and ovarian microbiome on IVF outcomes.Materials and Methods. The review was carried out based on publications from available in PubMed/MEDLINE, EBSCO, ResearchGate, Google Academy and еLibrary databases released over the last 20 years. For this, there was search for keywords and their combinations in Russian- and English-written publications: «vaginal microbiome», «cervical microbiome», «uterine microbiome», «ovarian microbiome», «microbiome of ovarian follicles», «IVF», «miscarriage», «early pregnancy loss», «implantation failure», «ovarian failure», «inflammasome». Only full-text original articles and reviews published in peer-reviewed journals were included in the review. Exclusion criteria were as follows: studies containing less than 10 observations per group, abstracts of conferences, studies on the male reproductive tract microbiome. Duplicate publicationswere excluded. The publications were selected independently by two co-authors, and in case of discrepancy two other co-authors were involved.Results. Vaginal, uterine, and ovarian microbiomes were characterized by providing relevant classifications and the features related to implantation failures and pregnancy loss after IVF. It was found that a decline in total Lactobacillus level and elevated proportion of L. jensenii, G. vaginalis, and Proteobacteria in the vaginal microbiome were predictors of implantation failure. In addition, IVF failure was also associated with the presence of Atopobium, Bifidobacterium, Chryseobacterium, Gardnerella, Streptococcus, Haemophilus, Staphylococcus, Brevundimonas, and Ralstonia in the uterine cavity as well as Bifidobacterium, Gardnerella, and Klebsiella in the endometrial tissue. On the other hand, Lactobacillus dominance in the uterine microbiome has a favorable effect. The colonization of the follicle by any microorganisms as well as the presence of follicular fluid anaerobic bacteria-derived metabolite trimethylamine-N-oxide (TMAO) associated with bacterial vaginosis additionally alters IVF outcomes. Moreover, the role of infectious cues in lowered ovarian reserve has also been established. Activation of the NLRP3 (NLR Family Pyrin Domain Containing 3) inflammasome by microbe-derived ligands stimulates production of pro-inflammatory cytokines and contributes to reduced follicle number. Blocking NLRP3 in mouse experiments can delay depletion of the follicle pool and result in elevated fertility.Conclusion. Favorable IVF outcomes are associated with Lactobacillus predominance in the vaginal and endometrial microbiome as well as lack of follicular fluid microorganisms. TMAO detected in the follicular fluid as well as activated NLRP3 inflammasome serve as negative predictors of IVF outcomes.